LAYANAN KONSELING INDIVIDUAL PENDEKATAN CLIENT CENTERED BERBASIS DALAM JARINGAN (DARING) UNTUK MENGEMBANGKAN CITRA DIRI (SELF IMAGE) SISWA - Adinda Zathnani Hikmah; Ika Mustika; Ecep Supriatna (IKIP Siliwangi, 2023)
Self image is a person's self concept which includes the physical and intelligence that is displayed to the people around him. One of the characteristics of high school students' puberty is that they want to show their existence, one of which is by displaying a self-image, but in reality the self-image that is displayed is negative, such as low self-esteem, shyness and closing off. The role of BK teachers is to develop students' self-image by using individual counseling services with a client centered approach. This study aims to describe group guidance services with a client centered approach that can develop students' self-image. The research method used is descriptive qualitative. Data collection was done by interview and documentation. Data analysis used the Miles and Huberman analysis technique which consisted of three activities, namely data reduction, data presentation and data verification. The research results obtained include (1) the counseling service process begins by analyzing student problems, preparing RPL and setting a counseling schedule (2) Individual counseling services are carried out through zoom meetings and attended by one student, BK teacher and researcher (3) student responses are very good and feel helped by doing client centered approach counseling. Keywords: Self Image, Individual Service, Client Centered